ANALYSIS OF MAXIMUM SUSTAINABLE YIELD AND BIOECONOMICS IN THE MANAGEMENT SILVER POMFRET (PAMPUS ARGENTEUS) IN PANGANDARAN REGENCY - Alfarizan Ghifari M., M.
Silver pomfret is a commodity that is favored by fishermen as a fishing resource. This is due to the protein content of essential amino acids which is quite high and is beneficial for health when consumed, as well as the high selling price of white pomfret fish and the ability to enter the export market.and due to the high selling price of silver pomfret fish and the ability to enter the export market. However, with the high selling price and large demand, the catch of white pomfret fish in Pangandaran Regency waters is increasing, and there are concerns that this could lead to overfishing. This research aims to determine the characteristics of silver pomfret fish and the type of fishing gear used in open access fishing, determine the production level of silver pomfret fish caught in open access, determine the value of Maximum Sustainable Yield (MSY), Maximum Economic Yield (MEY), and open access (OA) silver pomfret fish commodities in the Pangandaran Regency Water Area, and determine the sustainability conditions of white pomfret fish in the Pangandaran Regency Water Area. The method in this research is a case study with primary data and secondary data. Primary data was obtained from interviews with fishermen. Secondary data was obtained from the Ministry of Maritime Affairs and Fisheries in the form of data on fish catches in Pangandaran Regency for 5 years ranging from 2018 to 2022. The data obtained was processed and analyzed using biotechnical, bioeconomic and economic parameters. The results of the research show that the most effective fishing gear in catching silver pomfret is the beach seine with an FPI value of 1. Biological parameters obtained using the Walter-Hilbon Method are an r value of -6.024, a q value of 0.0002, and a K value of 0. 0045 . The utilization rate of silver pomfret fish is 446%. Based on the MSY, MEY, and OA calculations, it was found that the MSY condition is the most appropriate condition to be applied to silver pomfret fishing because it pays attention to the sustainability of silver pomfret fish. In the analysis of economic parameters, the average CPI was found to be 42.91, with a real input price of IDR 957,201 and a real output price of IDR 2,377,094,991. It was found that the silver pomfret fishery was experiencing overfishing, and needed further management to maintain its sustainability.